Do corporate tax cuts reduce international profit shifting - Laura Brandstetter (Arbeitskreis Quantitative Steuerlehre (arqus), 2014)
This paper analyzes whether a corporate tax cut reduces profit shifting to low-tax countries. I use firm-level data of 2,812 German corporations around the Business Tax Reform in 2008. Applying a difference-in-differences framework with a one-onone matching strategy, which compares earnings of multinational and domestic corporations, I do not find empirical evidence that even a 10 percentage points cut in the business tax rate leads to a reduction of profit shifting activities.
Keywords: F23; H25; H26; 330; corporate taxation; international profit shifting